2007
DOI: 10.1093/bioinformatics/btm061
|View full text |Cite
|
Sign up to set email alerts
|

POPI: predicting immunogenicity of MHC class I binding peptides by mining informative physicochemical properties

Abstract: A web server for prediction of peptide immunogenicity (POPI) and the used dataset of MHC class I binding peptides (PEPMHCI) are available at http://iclab.life.nctu.edu.tw/POPI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 30 publications
1
84
0
2
Order By: Relevance
“…Frequently, peptides are represented in binary format, but recently Tung and Ho [52] used the physicochemical properties of peptides known to bind to MHCI molecules as input data for SVMs, developing the POPI method (Table I). Similarly, Salomon and Flower [53] predicted MHCII-peptide binding using a kernel-based SVM that was trained on the similarity scores of MHCII allelic-specific peptide ligands.…”
Section: Machine Learning-based Motifsmentioning
confidence: 99%
“…Frequently, peptides are represented in binary format, but recently Tung and Ho [52] used the physicochemical properties of peptides known to bind to MHCI molecules as input data for SVMs, developing the POPI method (Table I). Similarly, Salomon and Flower [53] predicted MHCII-peptide binding using a kernel-based SVM that was trained on the similarity scores of MHCII allelic-specific peptide ligands.…”
Section: Machine Learning-based Motifsmentioning
confidence: 99%
“…Since the metabolic activation of PAHs could induce higher genotoxicity [30], additional biological features such as Ames tests with the addition of microsomal S9 fraction for metabolic activations of PAHs might serve as useful features for improving the prediction performance. Advanced machine learning methods combined with feature selection algorithms such as support vector machine and genetic algorithm could be further applied to further improve the prediction performance [31,32]. This study demonstrated a potential application of such models for predicting bioactivity of mixtures by combining chemical and biological features and could be further developed for other bioactivities.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the idea of producing anti-peptide antibodies in rabbits and BALB/c mice using the validated protocol with the High III mice cannot be ruled out. Although the antibody response was obtained for both immunogens in the High III mice, the high anti-Let#1 antibody titer compared with the anti-Let#2 antibody titer and the higher affinity may be justified by testing the immunogenicity prediction (POPI 2.0) [65], which indicates this peptide is more efficient as an immunogen with potential epitopes that are recognized by CD4 + T cell receptors. Furthermore, these antibodies were quite specific and did not react in a cross-evaluation with other antigens, suggesting that the method is efficient for validating these antibodies as potential identifiers of the native NaPi-IIb protein.…”
Section: Discussionmentioning
confidence: 98%